Genetic Susceptibility, Change in Physical Activity, and Long-term Weight Gain - T. Wang; Huang, T.; Heianza, Y.; Sun, D.; Zheng, Y.; W. Ma; Jensen, M. K.; Kang, J. H.; Wiggs, J. L.; Pasquale, L. R.; Rimm, E. B.; Manson, J. E.; et al. (DiabetesDiabetesDiabetes, 2017)
Whether change in physical activity over time modifies the genetic susceptibility to long-term weight gain is unknown. We calculated a BMI-genetic risk score (GRS) based on 77 BMI-associated single nucleotide polymorphisms (SNPs) and a body fat percentage (BF%)-GRS based on 12 BF%-associated SNPs in 9,390 women from the Nurses' Health Study (NHS) and 5,291 men from the Health Professionals Follow-Up Study (HPFS). We analyzed the interactions between each GRS and change in physical activity on BMI/body weight change within five 4-year intervals from 1986 to 2006 using multivariable generalized linear models with repeated-measures analyses. Both the BMI-GRS and the BF%-GRS were associated with long-term increases in BMI/weight, and change in physical activity consistently interacted with the BF%-GRS on BMI change in the NHS (P for interaction = 0.025) and HPFS (P for interaction = 0.001). In the combined cohorts, 4-year BMI change per 10-risk allele increment was -0.02 kg/m(2) among participants with greatest increase in physical activity and 0.24 kg/m(2) among those with greatest decrease in physical activity (P for interaction < 0.001), corresponding to 0.01 kg versus 0.63 kg weight changes every 4 years (P for interaction = 0.001). Similar but marginal interactions were observed for the BMI-GRS (P for interaction = 0.045). Our data indicate that the genetic susceptibility to weight gain may be diminished by increasing physical activity.
Keywords: *Body Mass Index; Adult; Aged; Body Weight; Exercise/*physiology; Female; Genetic Predisposition to Disease/genetics; Humans; Male; Middle Aged; Prospective Studies; Weight Gain/genetics/physiology